Mixed-addenda polyoxometalates for enhanced electrochemical water oxidation - Ong, Boon Chong (2022)
In this study, mixed-addenda polyoxometalates (POMs) were synthesized by self-assembly process accompanied by the introduction of dopants to boost the electrochemical water oxidation performance. A lower onset potential and higher current density were achieved by mixed-addenda POMs compared to pristine POMs suggesting that the former were more active towards the water oxidation reaction. It was found that at the same applied potential, the induced current of mixed-addenda POMs was almost threefold that of unmodified POMs. A steady current that was attained over several sweep cycles indicating the stability of mixed-addenda POMs. This work provides an insight into future prospective of mixed-addenda POMs as robust water oxidation catalyst under a neutral working environment. The presence of both tungsten and molybdenum as addenda atoms in POMs have tuned their properties and a variety of mixed-addenda POMs can be fabricated through precise control on the synthesis condition to better facilitate a specific application.